PERSON JOB-FIT AND EMPLOYEE RETENTION IN TERTIARY INSTITUTIONS IN KOGI STATE, NIGERIA (Journal of the Management Sciences, 2025)
This study investigated the relationship between person-job fit and employee retention in tertiary institutions in Kogi State, Nigeria, with a specific focus on the link between team fit and team dynamics. A descriptive survey research design was adopted, and data were collected using a structured questionnaire. The sample size was determined using Krejcie and Morgan’s table, while hypotheses were tested with the Pearson Product Moment Correlation Coefficient in SPSS version 27. Findings revealed a statistically significant positive relationship between team fit and team dynamics in the studied institutions. The study recommends that management of tertiary institutions should prioritize team fit in the formation and management of teams, as this enhances team dynamics and contributes to improved organizational performance.
Keywords: Person Job-Fit; Employee Retention; Team Fit; Team Dynamics; Tertiary Institutions